Remittances as investment in the absence of altruism - Gabriel González-König (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2005)
In the absence of altruism, there is no obvious reason why a migrant should remit part of his income to his family for investment at the home location. If the family invests such income (in housing for example), why would they give it back to the migrant when he returns? This paper is based on the idea that certain people at a migrant's home location may punish those families who do not return those investments in order to prevent their own possibilities of receiving future remittances and investments from being adversely affected. We find that in equilibrium we can have remittances to be invested and given back to the migrant and remittances for private consumption by the migrant's family even in the complete absence of altruism on either the part of the migrant or his family.
Keywords: J61; 330; Remittances; Altruism; Migration; Rücküberweisung (Migranten); Altruismus; Theorie; Migrationstheorie